Análise multiescalar do contexto das cavernas nas bacias hidrográficas dos rios Tocantins/Araguaia, Paranã e São Vicente - Fernanda Cristina Rodrigues de Souza (2020)
Multiscale research on the cave’s areas of influence has been discussed and investigation criteria established, at local and regional levels, for the purposes of environmental licensing. The importance of in-depth analyses on the reach of the areas influenced by the caves is stated, mainly for scientific purposes. Therefore, this work aims to analyze, in a multiscale way, the lithostructural and geomorphological context associated with caves developed from carbonate rocks in the hydrographic basins of the Tocantins/Araguaia, Paranã and São Vicente rivers. The methodological procedures used consisted of the following steps: a) a bibliographic review; b) a study of physiographic characteristics and their relationship with cave distribution in the Tocantins/Araguaia River hydrographic basin; c) interpretation of the main factors linked to the development of karst relief in the Paranã River hydrographic basin; d) research on the characteristics and development factors of the São Vicente I grotto; e) interpretation of spatial scales in the geomorphological research on the studied hydrographic basins. It has been observed that the caves developed in carbonate rocks in the Tocantins/Araguaia river basin are associated with lithologies belonging to the Bambuí Group and the Xambioá Group or to the contact between rocks of the Bambuí Group and the Paranoá Group. In this study’s scale, the caves appear to develop in areas with faults, folds and fractures. Most of the caves develop in areas such as São Francisco, Planalto Central and Planalto dos Guimarães plateaus. The Paranã River hydrographic basin has sets of caves linked to the carbonate rocks of the Bambuí Group, Lagoa do Jacaré Formation. The plateau areas, characterized by declivities of between 8% and 45%, and their geographical position close to the cuesta front, lend themselves to the development of the caves. In this study’s scale, the caves develop in fractured areas, but it is not possible to make assumptions about the structural contributions in determining the speleological planimetric pattern. In the São Vicente River hydrographic basin, different phases of evolution of the karst relief can be identified: 1) karst relief composed of massifs, sinkhole, resurgence, lapies and caves, where there is a predominance of dissolution and upwards erosion; 2) flat to smooth wave relief, interspersed with mogotes and surface drainage; 3) flat relief with plains, deep soils, superficial drainage and predominance of depositional processes. In this area, most of the caves are located in the Serra do Calcário, which is made up of clusters of limestone, dolomites, marls and breaches in the Sete Lagoas Formation, Bambuí Group. The lithological beddings are the main types of structures that allow water infiltration and the formation of the São Vicente I grotto. The planimetric morphology of São Vicente I grotto shows that its development comes mainly from the geochemical activity exerted by the action of the São Vicente river upon the friable and porous carbonate rocks that form Serra do Calcário. The analyzed spatial scale is proportional to the level of detail of the geomorphological information obtained. In the hydrographic basins of the São Vicente and Paranã rivers, it has been observed that the caves are directly associated with the development of the surrounding relief, especially because the caves, sinkholes and carbonate massifs function as base levels that control the expansion processes of these basins. The hydrographic basin of the Tocantins/Araguaia river, in turn, is indirectly influenced from the caves, since geotectonic events exercise the predominant controls over the dynamics of the relief in this area. However, the expansion of the Tocantins/Araguaia river hydrographic basin, in the southeastern part, is associated with the structuring of the front cuesta of Goiás, Tocantins and Bahia (Serra Geral de Goiás and Tocantins), the development of the caves and the karst relief. It is therefore suggested that multiscale studies in karst areas include: a geomorphological unit, a speleological unit and hydrographic units.